A Documentary History of Communism in Russia : From Lenin to Gorbachev - Daniels, Robert V. (Robert Vincent), 1926-2010 (Book collections on Project MUSE., 1993)
An extensive revision of the valued but unobtainable 1960 edition. Nearly 300 key documents are now readily available in translation.